Penggunaan Media Sosial Dalam Penyebaran Narasi Hak Asasi Manusia Di Indonesia: The Use of Social Media in Spreading Human Rights Narration in Indonesia - Misran Misran (JOURNAL OF GOVERNMENT SCIENCE, 2021)
This research looks into the kinds of social media used in human rights activism in Indonesia. To analyze social media data, Nvivo 12Plus as a qualitative data analysis software is used. The findings show that: 1) The  social media content and related discussions on citizen’s rights are dominated by human rights content; 2) activists’ social media accounts are connected, and the relationship is strong, which can be seen in 0,7 Lower limit; 3) narration in social media spreads using the acronym HAM (Hak Asasi Manusia [Human Rights]). To strengthen similar research in this area, social media data might be combined with digital data like the online newspapers. In addition, the comparison with another case and/or another country may give new novelty of the research.